Studi Komparatif: PP 23 Tahun 2018 dan UU 36/31E Tahun 2008 pada CV Saribumi - Prelina Nugraini, Dili; Setyopertiwi, Retno; Ernawati Adisiswanto, Alissa (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam Jember, 2025)
The objective of this study is to make a comparison between the tax burden and tax administration of CV Saribumi, with a particular focus on the application of PP 23/2018 and Law No. 36/31E. The research background is predicated on the dilemma faced by business entities in choosing the most profitable and efficient tax regulation, given the differences in schemes, rates, and administrative complexity in the two regulations. The research method employs a comparative approach, utilising data collection techniques such as interviews, observation, and documentation. The findings indicate that the implementation of PP 23/2018 results in a higher tax burden compared to Law No. 36/31E. The discrepancy is estimated to be approximately Rp. 49,752,643 in 2022, Rp. 122,187,908 in 2023, and Rp. 205,827,593 in 2024. It is evident that the administration of taxes in accordance with PP 23/2018 is a more efficient process when compared with the administration of taxes in accordance with Law No. 36/31E. This discrepancy is undoubtedly a salient consideration for CV Saribumi in its corporate tax reporting.The research concludes that PP 23/2018 is more suitable for business entities with characteristics such as CV Saribumi, providing tax burden efficiency and administrative convenience that supports business growth.